(untitled) - Ledyard, Gleason H.; (1919-2006) (Belarus, 1997)
Those who worked on this limited vocabulary NEW LIFE Version were constantly watching to make it understandable without sacrificing accuracy. There was no thought to changing God's Holy Word into today's street language. In fact, in many places, the wording and beauty of older versions have been retained. Paraphrasing, or man's idea of what the Bible says, was ruled out. The careful and prayerful use of some basic words can be made to say what the original languages said, thus assuring the reader of an accurate text.
Keywords: Bible -- Ledyard